c y Douglas Wood ; pictures by Doug Cushman. - Wood, Douglas, 1951- (New York, N.Y. : Simon & Schuster Books for Young Readers, 2000)
Describes how dads show love by explaining all the things that they cannot do, such as sleeping late, keeping their ties clean, and reading books by themselves.
Keywords: Fathers